Effect of probiotics supplementation on glucose and oxidative stress in type 2 diabetes mellitus: a meta-analysis of randomized trials - Ardeshirlarijani, Edris; Tabatabaei-Malazy, Ozra; Mohseni, Shahrzad; Qorbani, Mostafa; Larijani, Bagher; Baradar Jalili, Reza (Daru, 2019)
Purpose The role of oxidative stress in pathogenesis of diabetes is well established. In addition, an association between gut microbiota and type 2 diabetes mellitus (T2DM) is widely observed in previously published reports. This meta-analysis critically examines the association between gut microbiota, and oxidative stress in T2DM. Methods A systematic search for clinical trials was performed in PubMed, Web of Science and Scopus web databases up to 1 Jan 2019. Primary search terms include “microbiota”, “diabetes”, and “oxidative stress”. Study was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline. All clinical trials that compared the effects of probiotic supplementations with a control group using end points serum levels of fasting blood sugar (FBS), hemoglobin A1C (HbA1C) and oxidative stress biomarkers were included. Two independent researchers screened the data extracted from the relevant studies. The pooled standardized mean difference (SMD) was estimated using the random or fixed effects model. Heterogeneity among the studies was assessed using Q-test. Results Overall, 13 randomized clinical trials (RCTs) involving 840 subjects with T2DM were included in the meta-analysis. The analysis showed that probiotics intake resulted in significant improvement in serum levels of FBS [SMD: -0.35, 95% CI: (−0.59, −0.12)], total antioxidant status (TAS) [SMD: 0.33, 95% CI: (0.11, 0.55)], total glutathione (GSH) [SMD: 0.41, 95% CI: (0.26, 0.56)] and malondialdehyde (MDA) [SMD: -0.54, 95% CI: (−0.83, −0.26)]. No significant improvement was found in HbA1C [SMD: -0.06, 95% CI:(−0.82, 0.69)], and nitric oxide (NO) [SMD:-0.24, 95% CI:(−1.10, 0.62)] levels. Conclusion It seems that gut microbiota can exert beneficial effects in diabetic patients via altering oxidative stress’ biomarkers. The beneficial effect of gut microbiota however was modest on FBS and non-significant on HbA1C. These results need to be confirmed by conducting more reliable RCTs. PROSPERO Registration number CRD42019134905. Graphical abstract Flow diagram of the study selection process.